Removal of total ammonia nitrogen (TAN), nitrate and total organic carbon (TOC) from aquaculture wastewater using electrochemical technology: A review - Mook, W.T.; Chakrabarti, M.H.; Aroua, M.K.; Khan, G.M.A.; Ali, B.S.; Islam, M.S.; Abu Hassan, M.A. (Desalination, 2012)
Protein rich wastes from aquaculture systems result in total ammonia nitrogen (TAN), total organic carbon (TOC) and biochemical oxygen demand (BOD). A number of conventional approaches have been adopted for the removal of these wastes in aquaculture ponds and hatcheries with varying degrees of success but they face critical problems such as membrane fouling, high cost or the generation of toxic by-products. To overcome such issues, electrochemical technology is commonly employed. The advantages of electrochemical treatment include high efficiency, ambient operating conditions, small equipment sizes, minimal sludge generation and rapid start-up. An even better system involves bio-electrochemical reactors (BERs), which have the potential to generate energy from wastewater (by means of microbial fuel cells) or a valuable product such as hydrogen (using microbial electrolysis cells). Mechanisms of cathodic nitrate reduction and anodic oxidation in electrochemical and bio-electrochemical technology are reported in this review. Also some work on the simultaneous removal of nitrate and organic matter by Electro-Fenton and microbial fuel cells are elaborated upon. It is apparent that BERs can remove contaminants at high efficiencies (≈ 99%) whilst giving least impact upon the environment.